Awake orotracheal fibre-optic intubation: Comparison of two different doses of dexmedetomidine on intubation conditions in patients undergoing cervical spine surgery - Jaya Sharma (Indian Journal of Anaesthesia, 2017)
Background and Aims: Awake fibre-optic intubation (AFOI) is an integral part of anaesthetic management of difficult airways. Conscious sedation is essential to assist AFOI. This study compared two different doses of dexmedetomidine in combination with topical spray and airway blocks for awake orotracheal fibre-optic intubation in patients undergoing elective cervical spine surgery with rigid cervical collar in situ. Methods: A randomized, prospective, comparative study design was conducted in sixty patients divided into two groups: Group (L) (n = 30) patients received low dose of dexmedetomidine (0.5 μg/kg) along with airway blocks and Group (H) (n = 30) patients received standard dose of dexmedetomidine (1 μg/kg) along with airway blocks. Both the groups received dexmedetomidine infusion over 10 min followed by airway block. Quantitative data were analysed by applying Student's t-test whereas qualitative data were analysed with Chi-square test. The objectives were to compare patients' Observer's Assessment of Alertness/Sedation scale (OAA/S) as primary outcome and other variables such as endoscopy, intubation condition, tolerance and haemodynamic stability among low and standard doses of dexmedetomidine. Results: Group H had more favourable OAA/S score than that of Group L, but endoscopy and intubation time, patient tolerance, vocal cord and limb movement and satisfaction score did not differ significantly between the groups. There were no significant haemodynamic differences between the two groups. Conclusion: The 0.5 μg/kg dose of dexmedetomidine was found optimal and effective in combination with topical spray and airway blocks for awake orotracheal fibre-optic intubation for patients undergoing elective cervical spine surgery.